2016
DOI: 10.4132/jptm.2015.10.31
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Aquaporin 5 Expression in Non-small Cell Lung Cancer

Abstract: Background:Aquaporins are water channel proteins that play a major role in the movement of water in various human tissues. Recently, it has been found that aquaporins have influence in the carcinogenesis of human malignancies. We analyzed the prognostic impact of aquaporin 5 (AQP5) in non-small lung cancer (NSCLC).Methods:Seventy-six cases of NSCLC were studied, including 44 cases of adenocarcinoma (ADC) and 32 cases of squamous cell carcinoma (SQCC). Tissue microarray was constructed and immunohistochemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In the present study, it was observed that AQP5 was highly expressed in H1299, a NSCLC cell line. This observation is in line with previous findings suggesting the upregulation of AQP5 in lung adenocarcinoma cells (14). In clinical settings, AQP5 upregulation is considered as a sign of poor cancer prognosis (2,19).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, it was observed that AQP5 was highly expressed in H1299, a NSCLC cell line. This observation is in line with previous findings suggesting the upregulation of AQP5 in lung adenocarcinoma cells (14). In clinical settings, AQP5 upregulation is considered as a sign of poor cancer prognosis (2,19).…”
Section: Discussionsupporting
confidence: 93%
“…The expression of human AQP1 has been found to be unaffected in brain tumors, renal cell carcinoma, colon cancer and pancreatic cancer, whereas AQP5 expression was identified to be increased in lung, salivary glands and kidney cancer (10). In addition, AQP5 is increased in ovarian and cervical cancer, esophageal squamous cell carcinoma, and hepatocellular carcinoma; however, lymphocyte activation stimulates the transcription of AQP1, AQP3 and AQP5 (11)(12)(13)(14). AQPs play an important functional role in cell migration in various cell types, including brain, pancreas and colon cancer cells (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…There is a linkage between smoking habits and KRAS mutations, with an incidence of 25–35% in smokers and only 5% in never-smokers [ 27 29 ]. Approximately, 97% of KRAS mutations interest codons 12 and 13 in exon 1, less frequently, mutations occur at codon 61 (Table 1 ) [ 30 32 ]. While these mutations are located near to the GTP binding site, the intrinsic GTP-ase activity is impaired and KRAS accumulates in GTP-bound constitutively active form, which sustains the activation of the KRAS downstream signalling [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of AQP5 was found in a variety of cancers, including non-small cell lung cancer, ovarian cancer, prostate cancer and cervical cancer (Chae et al 2008;Pust et al 2016;Tiwari et al 2014;Zhang et al 2012). Moreover, the expression level of AQP5 was negatively correlated with the prognosis of patients with multiple carcinomas (Huang et al 2013;Jo et al 2016;Lee et al 2014;Li et al 2014;Yan et al 2014a). It has been demonstrated that AQP5 expression is elevated and proposed to be a novel biomarker that predicts poor clinical prognosis in colorectal cancer (Shan et al 2014;Wang et al 2012).…”
Section: Introductionmentioning
confidence: 99%